2015
DOI: 10.7860/jcdr/2015/11729.5689
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Fibrous Tumour of Lacrimal Gland: A Rare Entity

Abstract: A 52-year-old male presented to the ophthalmology outpatient department with complaints of swelling in the left supero-lateral aspect of the orbit (lacrimal gland region) for past two years. Patient gave history of gradual increase in size of the lesion. On examination, the swelling was apparently soft and non tender. He ruled out any history of trauma at this site. No associated ocular complaints were present. Routine investigations like Complete blood counts, Liver function tests, Renal function tests, Viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…SFTs arise in many locations of the orbital soft tissues, but commonly involve the superior area [ 1 ]. Since Scott et al [ 2 ] first reported SFT in the lacrimal gland fossa in 1996, there have only been 9 reported cases in the lacrimal gland fossa (table 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. We report a case of SFT in the lacrimal gland fossa presenting at a young age, including features of imaging, histological and immunohistochemical studies.…”
Section: Introductionmentioning
confidence: 99%
“…SFTs arise in many locations of the orbital soft tissues, but commonly involve the superior area [ 1 ]. Since Scott et al [ 2 ] first reported SFT in the lacrimal gland fossa in 1996, there have only been 9 reported cases in the lacrimal gland fossa (table 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. We report a case of SFT in the lacrimal gland fossa presenting at a young age, including features of imaging, histological and immunohistochemical studies.…”
Section: Introductionmentioning
confidence: 99%